Digitalization of SMEs: A Review of Opportunities and Challenges - Thrassou, Alkis; Uzunboylu, Naziyet; Vrontis, Demetris; Christofi, Michael (My University, 2020)
SMEs have always been hailed as economic drivers and the major employer, across industries and nations. And though receiving, perhaps, less attention than they deserve compared to their larger counterparts, their attributes, role and style have always intrigued business scholars. SMEs, however, have seen their identity and position against large companies and customers change drastically over the information technology revolution of the past two decades. A period that has partly weakened them against competition from large global companies, but which has also armed them with competencies and opportunities to do things and reach customers that were unimaginable in the recent past. This chapter undertakes a comprehensive review of extant scientific works to identify the range and nature of opportunities and challenges faced by SME in contemporary business in the context of digitalization and information and communication technological developments.
Keywords: Challenges; Communications technology; Digitalization; Information technology; Opportunities; SMEs